Effect of tea (Camellia sinensis) seed saponins on in vitro rumen fermentation, methane production and true digestibility at different forage to concentrate ratios. Issue 1 (1st January 2018) - Jadhav, R. V.; Kannan, A.; Bhar, R.; Sharma, O. P.; Gulati, A.; Rajkumar, K.; Mal, G.; Singh, B.; Verma, M. R.
ABSTRACT: The present study was conducted to evaluate the effect of tea ( Camellia sinensis ) seed saponins (TSS) on in vitro rumen fermentation with different forage to concentrate ratios in the in vitro gas production technique. Experimental treatments were a low forage diet (forage: concentrate = 30:70), a medium forage diet (forage: concentrate = 50:50) and a high forage diet (forage: concentrate = 70:30). TSS was added at levels of 0.0%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1.0% of substrate. Protozoal count, ammonia-N production and methane production decreased linearly up to the dose level of 0.8% in all the substrates. The maximum reduction obtained was 54.6%, 57.2% and 60.6% for protozoal counts; 29%, 33% and 36% for methane production; and 36.6%, 36.6% and 33.8% for ammonia-N production at low, medium and high forage diets, respectively. Net 24 h gas production, short chain fatty acid production, metabolizable energy value increased and in vitro true dry matter and organic matter digestibility significantly decreased due to addition of saponins. Results suggest that TSS has the potential to reduce methane production and positively impact rumen fermentation across different forage to concentrate ratios.